2017
DOI: 10.15740/has/ajhs/12.2/395-401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retting methods on properties ofDhaincha fibres

Abstract: :The dried ribbons of Sesbania aculeata (Dhaincha) plant were retted by chemical and biological retting methods. In first chemical retting method, the fibres were treated with the combination of EDTA and NaOH whereas in second method pretreated with HCl followed by NaOH; In biological retting method both the stagnant and running water methods were utilized. The retted fibres were tested for physical properties such as, moisture content and weightloss. The percentage weight loss was found to be more in case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The dhaincha fibres have also found useful as non-woven and could have prospects in the field of geotextiles (Singh and Rani, 2013) [17] . The chemical characterization of the plant revealed that it is composed of 21.94%, ash content 2.15%, fats and waxes 1.34%, holocellulose 73.6%, cellulose 42.2% hemicellulose 30.9% (Negi, 2017) [11] . The encrusting substance lignin glue the fiber cells together and provides strength to the plant and stiffness to fibres.…”
Section: Introductionmentioning
confidence: 99%
“…The dhaincha fibres have also found useful as non-woven and could have prospects in the field of geotextiles (Singh and Rani, 2013) [17] . The chemical characterization of the plant revealed that it is composed of 21.94%, ash content 2.15%, fats and waxes 1.34%, holocellulose 73.6%, cellulose 42.2% hemicellulose 30.9% (Negi, 2017) [11] . The encrusting substance lignin glue the fiber cells together and provides strength to the plant and stiffness to fibres.…”
Section: Introductionmentioning
confidence: 99%